The Role of Librarians in Supporting Academic Administration and Research at Polytechnic Adiguna Maritim Indonesia Medan - Jupriani, Jupriani; Riady, Yasir (Adabi : Journal of Public Administration and Business, 2024)
Libraries have an important role in supporting academic research. Librarians are not only tasked With managing information resources, but also play a role in assisting researshers in the process of searching for information, processing data, and publishing research result. The aim of this research is to identify the role of librarians in supporting academic research, both in terms of services, infrastructure and information literacy. The research result shows that the role of librarians is very important in increasing the effectiveness and efficiency of academic research. Information literacy and the proper use of electronic resources are two areas in which librarians may make a difference. Since it stores, processes, and provides the information sources required throughout the research process of its academic community, the library plays a crucial role as a supporting element of universities in research operations. However, up until now, the university library has mostly served as a repository for research findings and has played little to no role in the actual research process. First, the library should revitalise its reference collection in order to better assist researchers. 2. Providing academics with information literacy training, Thirdly, recording findings from studies.